INFLASI DARI SUDUT PANDANG MONETER DAN FISKAL (STUDI KASUS SUMATERA BARAT) - Zul Azhar; Alpon Satrianto; Nofitasari Nofitasari (Universitas Negeri Padang, 2019)
This study aims to analyze the effect of money supply M2, interest rate, government spending and local tax on the inflation in West Sumatera. This type of research is descriptive research and secondary datain the form of time-series from quartely 1 2007 to 2017 quartely 4 using the method of Autoregresive Distributed Lag analysis. The results of this study indicate that money supply in the long run have a significant and positive effect on inflation West Sumatera. In the short run and long run the interest rate has a significant and positive effect on inflation in West Sumatera. Government spending in the Long run has a significant and negative effect on inflation in West Sumatera. Based on the result of this study can be concluded that there is inflation in West Sumatera is monetery of phenomenon in the long run.